On the Hadamard product of balancing [Q.sup.n.sub.B] matrix and balancing [Q.sup.-n.sub.B] matrix - Ray, Prasanta Kumar; Swain, Sujata (TWMS journal of applied and engineering mathematics, 2015)
In this paper, the matrix [Q.sup.n.sub.B] x [Q.sup.-n.sub.B] which is the Hadamard product of both balancing [Q.sup.n.sub.B] matrix and balancing [Q.sup.-n.sub.B] matrix is introduced. Some properties of the Hadamard product of these matrices are investigated. A different coding and decoding method based on the application of the Hadamard product of balancing [Q.sup.n.sub.B] matrix and balancing [Q.sup.-n.sub.B] matrix is also considered Keywords: Balancing numbers, Balancers, Balancing Q-matrix, Cryptography AMS Subject Classification: 11B 39, 11B 83, 11T 71